Design of Financial Support and Capacity-Building Program for Rooftop Solar Photovoltaic in Turkey - World Bank (World Bank, Washington, DC, 2020)
Countries around the world are undergoing an unprecedented clean energy transformation, where Distributed Energy Generation (DEG) is an increasingly important player to achieve the paradigm shift. Rooftop solar PV (RSPV) represents an increasingly significant option of DEG, especially when coupled with storage, due to its contribution to: (i) reducing energy costs, (ii) viable renewable and carbon free energy, (iii) peak shaving, (iv) helping security of supply, (v) saving capital investment due to decreased system losses and (vi) increased reliability from brownouts, etc. A driver for DEG is the desire for the customer to become a more active participant (prosumer, demand response, time-of-use) in the electricity market. RSPV in Turkey is at a nascent stage. The solar market in Turkey has grown over the last few years with installed solar photovoltaic (PV) capacity growing from 40 MW in 2014 to about 5,063 MW at the end of 2018, benefiting from a feed-in-tariff of 13.3 cents/kWh. However, most solar projects are unlicensed, ground mounted and under 1 MW in size, to take advantage of ease with permitting. As of 2020, only 267 MW of RSPV had been installed in Turkey, mainly in large industrial and commercial establishments. In contrast, in countries with more developed solar markets, such as Germany, the United States, and Japan, a significant portion of solar capacity is produced by RSPV applications with 1 kW to 10 MW capacities. Given the fast pace of urbanization and corresponding residential, commercial, and industrial markets, there is significant potential for RSPV deployment in Turkey, which would help the country have more energy security through decentralized generation, create more jobs, and support clean energy transition.